PENGARUH NILAI DAN RATING PENERBITAN SUKUK SERTA DER PERUSAHAAN TERHADAP REAKSI PASAR - Ainurrochma, Elyya; Priyadi, Maswar Patuh (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Investors in the making of investment decision require information about the condition and the financial performance of the company. Information about the value and the rating of the issuance of sharia bonds (sukuk) and Debt to Equity Ratio (DER) is some alternatives to test whether this information influence to the market reaction.The population is all companies which have published their sharia bond and they have been listed in Indonesia Stock Exchange in 2006-2014 periods. This research is based on the criteria of purposive sampling and 12 go public companies have been selected as samples with the total 32 bond issuances of sharia bond (sukuk).This research has been conducted by using multiple linear regressions analysis technique and the assistance of SPSS (Stastistical Product and Service Solution) Program. The results of this research indicates that variables the rating of bond issuance of sharia bonds (sukuk) has an influence to the stock return. Meanwhile the variables i.e.: the value of bond issuance of sharia bonds (sukuk) and Debt to Equity Ratio (DER) do not have any influence to the stock return.Keywords : The value of bond issuance of sharia bonds (sukuk), rating of sharia bonds (sukuk), debt to equity ratio (DER), stock return.